2017
DOI: 10.1177/2167702617709812
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Away Disorder: The Influence of Context on Impressions of Mental Health Symptoms

Abstract: Clinical assessments involve understanding displays of mental disorder symptoms in the contexts in which they display. Contextual information plays a large role in externalizing disorder assessments. Yet we know little about contextual information's impact within internalizing disorder assessments. Panic disorder symptoms develop outside environmental effects, but over time symptoms become conditioned responses to one's environment, making this disorder an interesting test case. In two experiments (N = 269), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Informant reports are also limited in that the informant (e.g. parent, teacher) typically only observes the adolescent in a single context [95]. Use of mixed informants would also likely have acted as a confound since self and informant ratings are often only weakly or moderately correlated, particularly for children and adolescents [9698].…”
Section: Discussionmentioning
confidence: 99%
“…Informant reports are also limited in that the informant (e.g. parent, teacher) typically only observes the adolescent in a single context [95]. Use of mixed informants would also likely have acted as a confound since self and informant ratings are often only weakly or moderately correlated, particularly for children and adolescents [9698].…”
Section: Discussionmentioning
confidence: 99%
“…In recent experimental work, trained judges of children’s behavior (i.e., clinicians experienced in the assessment and treatment of child and adolescent mental health) were more likely to rate children described in vignettes as evidencing conduct problems if the environments in which these children lived contained risk factors for conduct problems (e.g., presence of parental mental health concerns) versus environments containing no such risk factors (De Los Reyes & Marsh, 2011). More recent work indicates that effects of contextual information generalize to clinicians’ judgments of other mental health domains (i.e., attention and hyperactivity; panic disorder), as well as laypeople’s judgments (Marsh, Burke, & De Los Reyes, 2016; Marsh & De Los Reyes, 2018; Marsh, De Los Reyes, & Wallerstein, 2014).…”
Section: Theory On Informants’ Subjective Reports In Mental Health Rementioning
confidence: 99%
“…mental health concerns) versus environments containing no such risk factors(De Los Reyes & Marsh, 2011). More recent work indicates that effects of contextual information generalize to clinicians' judgments of other mental health domains (i.e., attention and hyperactivity; panic disorder), as well as laypeople's judgments(Marsh, Burke, & De Los Reyes, 2016;Marsh & De Los Reyes, 2018;Marsh, De Los Reyes, & Wallerstein, 2014).…”
mentioning
confidence: 99%
“…The stimuli used in the first five articles are suitable for empirical research. In four of the five studies, they are vignettes (also called short clinical reports) of real disorders (Flores, Cobos, & Hagmayer, 2018 [this issue]; Marsh & De Los Reyes, 2018 [this issue]; Weine & Kim, 2018 [this issue]) or fictitious diseases (Hayes, 2018 [this issue]). Such stimuli approximate what clinicians will see in practice and allow the researcher to manipulate the relevant variables.…”
Section: Clinical Decision-making Researchmentioning
confidence: 99%
“…In mental health studies, no effect of domain experience on clinical performance has been found yet (cf. Marsh & De Los Reyes, 2018 [this issue]; see also Spengler et al, 2009; Suhr, 2015; Tracey, Wampold, Lichtenberg, & Goodyear, 2014). Does that mean that there are no “expert” clinicians?…”
Section: Further Researchmentioning
confidence: 99%